RESEARCH ON THE PRODUCTION OF MRNA ENCODING SLEEPING BEAUTY TRANSPOSASE IN CAR-T CELL ENGINEERING - Văn Mão Cấn; Lê, Cương (Tạp chí Y học Quân sự, 2025)
Objectives: To produce mRNA Encoding Sleeping Beauty Transposase from the DNA Template Plasmid pSB100X. Subjects and methods: The gene encoding the Sleeping Beauty (SB) transposase protein was amplified from the DNA template plasmid pSB100X using PCR. The PCR product was then directly purified using the QIAquick PCR Purification Kit (Qiagen). In vitro transcription of mRNA was performed using T7 polymerase (New England Biolabs) with optimized incubation times of 2 hours, 6 hours, and 15 hours, and varying enzyme concentrations of 10 U, 30 U, and 100 U to determine optimal conditions. The final mRNA product was purified and subjected to Sanger sequencing at Macrogen (Seoul, South Korea). Results: In vitro transcription for 2 hours produced a significantly higher yield of mRNA encoding the SB100X protein compared to reactions conducted for 30 minutes or 1 hour (p < 0.05). The resulting mRNA appeared as a distinct, specific band corresponding to an approximate size of 1,200 bp. The optimal amount of T7 polymerase for each transcription reaction was determined to be 30 U. After purification, the transcribed mRNA was subjected to Sanger sequencing at Macrogen (Seoul, South Korea), yielding a specific band of approximately 1,200 bp with a sequence that was completely accurate. Conclusion: mRNA encoding the SB transposase was successfully produced with high purity and correct sequence, using 30 U of enzyme after 15 hours of in vitro transcription.